THE EFFECTS OF LEARNING METHOD AND MOTIVATION TOWARDS ENGLISH SPEAKING SKILLS AT SMP NEGERI EAST JAKARTA - Nurzanah Nurzanah; Supadi Supadi (INFERENCE: Journal of English Language Teaching, 2018)
The purposes of this research are (1) to find out  the learning methods towards  English speaking skills of  SMP Negeri Students in East Jakarta. 2) to find out the motivation towards English speaking skills of SMP Negeri students in East Jakarta. 3) to find out the interaction of learning methods and motivation towards English speaking skills of SMP Negeri students in East Jakarta. The method used in this study is an experiment.. By using two different classes, namely the control class and the experimental class which shows the motivation and learning outcomes of students' English speaking skills at SMP Negeri in East Jakarta. The sampling is done by random sampling technique. The number of  population is  502 students while  25 respondents as sample. The research instrument used is a questionnaire and test of English speaking skills at SMP Negeri in East Jakarta. The results showed that; 1) there is a significant effect of learning methods towards the English speaking skills of  SMP Negeri in  Jatinegara area of East Jakarta. This is evidenced by the acquisition of Sig. = 0.007 <0.05 and Fh = 8.040. 2) There is a significant influence of motivation towards English speaking skills of SMP Negeri in  Jatinegara area of East Jakarta. This is evidenced by the acquisition of Sig. = 0,000 <0.05 and Fh = 28,072. 3) There is a significant interaction effect of learning methods and motivation towards  English speaking skills of SMP Negeri in Jatinegara area of East Jakarta. This is evidenced by the acquisition of Sig. = 0.036 <0.05 and Fh = 4.662.